PENGATURAN DAN MEKANISME PEMBERIAN KOMPENSASI, RESTITUSI DAN REHABILITASI DALAM TINDAK PIDANA TERORISME - Winda Sandra Devi, A. A. Ayu; Novi Purwanto, I Wayan (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 01, Maret 2014)
This paper titled granting Restitution, Compensation and Rehabilitation for victims of terrorist acts. This paper uses analyticalmethods and normative legislation approaches, in this current period crime has become a phenomenon that can be understood in different sides. Each country is given a right to decide where the decision is considered crucial in preventing the occurrence of a crime that endangers the lives of many people and countries. As well as criminal acts of terrorism, where the terror is carried out by certain elements for personal use and the problem of terrorism to be one form of threat to the world security. In this case should also think about how the process of the victims gain restitution, compensation and rehabilitation.
Keywords: Terrorism, Crime, Restitution,Compensation